Effects of 7-week Resistance Training on Handcycle Performance in Able-bodied Males - Abonie, Ulric Sena; Albada, Tryntje; Morrien, Floor; van der Woude, Lucas; Hettinga, Florentina (International Journal of Sports Medicine, 2021)
The effect of an upper body resistance training program on maximal and submaximal handcycling performance in able-bodied males was explored. Eighteen able-bodied men were randomly assigned to a training group (TG: n=10) and a control group (CG: n=8). TG received 7 weeks of upper body resistance training (60% of 1 repetition maximum (1RM), 3×10 repetitions, 6 exercise stations, 2 times per week). CG received no training. Peak values for oxygen uptake (V˙O2peak), power output (POpeak), heart rate (HRpeak), minute ventilation (V˙OEpeak) and respiratory exchange ratio (RERpeak), submaximal values (HR, V˙O2, RER, PO, and gross mechanical efficiency (GE)), and time to exhaustion (TTE) were determined in an incremental test pre- and post-training. Maximal isokinetic arm strength and 1RM tests were conducted. Ratings of perceived exertion (RPE) were assessed. A two-way repeated measures ANOVA and post-hoc comparisons were performed to examine the effect of time, group and its interaction (p<0.05). TG improved on POpeak (8.55%), TTE (10.73%), and 1RM (12.28–38.98%). RPE at the same stage during pre- and post-test was lower during the post-test (8.17%). Despite no improvements in V˙O2peak, training improved POpeak, muscular strength, and TTE. Upper body resistance training has the potential to improve handcycling performance.
Keywords: rehabilitation; handbiking; wheelchair user; physical capacity evaluation; upper body training